Outcomes of primary refractory diffuse large B‐cell lymphoma (DLBCL) treated with salvage chemotherapy and intention to transplant in the rituximab era. (16th December 2016) - Vardhana, Santosha A.; Sauter, Craig S.; Matasar, Matthew J.; Zelenetz, Andrew D.; Galasso, Natasha; Woo, Kaitlin M.; Zhang, Zhigang; Moskowitz, Craig H.
Summary: Rituximab‐containing salvage chemotherapy followed by high‐dose therapy and autologous stem cell transplant (ASCT) in chemosensitive patients remains the standard of care for patients with relapsed and refractory diffuse large B‐cell lymphoma (DLBCL). However, its role in those patients achieving less than a complete response to first‐line therapy (primary refractory disease) in the rituximab era is not well defined. We reviewed the outcomes of 82 transplant‐eligible patients with primary refractory DLBCL who underwent salvage therapy with the intent of administering high‐dose therapy and ASCT to patients achieving chemosensitive remission. The estimated 3‐year overall and progression‐free survival for all patients was 38% and 29%, respectively, and 65% and 60% respectively for patients proceeding to stem cell transplant. Long‐term remission was achieved in 45% of patients achieving a partial response (PR) to initial induction therapy and <20% of patients with stable or progression of disease following initial therapy. These results suggest that salvage chemotherapy with the intent of subsequent high‐dose therapy and ASCT remains a feasible strategy in certain patients with primary refractory DLBCL, particularly for those achieving a PR to frontline therapy. The primary barrier to curative therapy in patients with primary refractory disease is resistance to salvage therapy, and future studies should be aimed towards increasing the response rate in this population.